Aggregation‐Induced Emission Gold Clustoluminogens for Enhanced Low‐Dose X‐ray‐Induced Photodynamic Therapy. (5th September 2019) - Sun, Wenjing; Luo, Li; Feng, Yushuo; Cai, Yuting; Zhuang, Yixi; Xie, Rong‐Jun; Chen, Xiaoyuan; Chen, Hongmin
Abstract: The use of gold nanoparticles as radiosensitizers is an effective way to boost the killing efficacy of radiotherapy while drastically limiting the received dose and reducing the possible damage to normal tissues. Herein, we designed aggregation‐induced emission gold clustoluminogens (AIE‐Au) to achieve efficient low‐dose X‐ray‐induced photodynamic therapy (X‐PDT) with negligible side effects. The aggregates of glutathione‐protected gold clusters (GCs) assembled through a cationic polymer enhanced the X‐ray‐excited luminescence by 5.2‐fold. Under low‐dose X‐ray irradiation, AIE‐Au strongly absorbed X‐rays and efficiently generated hydroxyl radicals, which enhanced the radiotherapy effect. Additionally, X‐ray‐induced luminescence excited the conjugated photosensitizers, resulting in a PDT effect. The in vitro and in vivo experiments demonstrated that AIE‐Au effectively triggered the generation of reactive oxygen species with an order‐of‐magnitude reduction in the X‐ray dose, enabling highly effective cancer treatment. Abstract : Krebstötende Cluster : Gold‐Clustoluminogene (AIE‐Au) mit aggregationsinduzierter Emission wurden für die röntgeninduzierten photodynamischen Therapie entwickelt. Die AIE‐Au zeigen eine starke Strahlungsabsorption und erzeugen effizient Hydroxylradikale, die den radiotherapeutischen Effekt verstärken. Zusätzlich regt die röntgeninduzierte Lumineszenz der AIE‐Au konjugierte Photosensibilisatoren an, ein PDT‐Effekt wird hervorgerufen.